2015
DOI: 10.1016/j.compbiomed.2015.06.008
|View full text |Cite
|
Sign up to set email alerts
|

Multimodal data and machine learning for surgery outcome prediction in complicated cases of mesial temporal lobe epilepsy

Abstract: Background This study sought to predict postsurgical seizure freedom from pre-operative diagnostic test results and clinical information using a rapid automated approach, based on supervised learning methods in patients with drug-resistant focal seizures suspected to begin in temporal lobe. Method We applied machine learning, specifically a combination of mutual information-based feature selection and supervised learning classifiers on multimodal data, to predict surgery outcome retrospectively in 20 presurg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
66
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(74 citation statements)
references
References 73 publications
1
66
0
Order By: Relevance
“…More recently, Armañanzas et al compared k ‐NN and Naïve Bayes classifiers in predicting Engel I vs II–III outcomes using similar presurgical data, although with the notable addition of a larger neuropsychological battery that included personality style as assessed using a Rorschach test; after narrowing the classifiers to the three most informative variables (including personality style), the authors noted predictive accuracies of 89.47% with either classifier . Memarian et al instead compared linear discriminant analysis with Naïve Bayes and SVM classifiers in examining preoperative clinical, electrophysiologic, and structural MRI data from 20 patients, noting highest accuracy (of 95%) in predicting Engel I outcomes using a least‐square SVM classifier . In contrast, a study utilizing an SVM classifier only on T1‐weighted MRI sequences from 49 patients demonstrated 100% sensitivity and 88%‐92% specificity (in male and female cohorts, respectively) in predicting postsurgical seizure freedom .…”
Section: Applications In Surgical Management Of Epilepsymentioning
confidence: 99%
“…More recently, Armañanzas et al compared k ‐NN and Naïve Bayes classifiers in predicting Engel I vs II–III outcomes using similar presurgical data, although with the notable addition of a larger neuropsychological battery that included personality style as assessed using a Rorschach test; after narrowing the classifiers to the three most informative variables (including personality style), the authors noted predictive accuracies of 89.47% with either classifier . Memarian et al instead compared linear discriminant analysis with Naïve Bayes and SVM classifiers in examining preoperative clinical, electrophysiologic, and structural MRI data from 20 patients, noting highest accuracy (of 95%) in predicting Engel I outcomes using a least‐square SVM classifier . In contrast, a study utilizing an SVM classifier only on T1‐weighted MRI sequences from 49 patients demonstrated 100% sensitivity and 88%‐92% specificity (in male and female cohorts, respectively) in predicting postsurgical seizure freedom .…”
Section: Applications In Surgical Management Of Epilepsymentioning
confidence: 99%
“…Nevertheless, those findings had limited clinical applications. Machine learning can be adopted for single subject prediction and has shown significant potential for disease diagnosis [69][70][71][72] at the individual level.…”
Section: Discussionmentioning
confidence: 99%
“…18,28,29 To evaluate semiology, movements can be analyzed using accelerometry, surface electromyography, video detection systems, mattress sensor, and seizure-alert dogs; physiological signals can be evaluated by electrocardiography, skin temperature, audio classification, and respiratory rate changes techniques. 33,34 These techniques are used to extract features and to perform a decision using electrophysiological signals. 18 Video detection systems and electroencephalography have been considered the gold standard for the diagnosis of seizures.…”
Section: Traditional Approaches To Automatic Epilepsy Evaluationmentioning
confidence: 99%
“…Researchers have implemented machine learning algorithms and different detection devices to increase the performance of epilepsy tasks, including epilepsy diagnosis, 30,31 automatic classification of epilepsy types, 32 and outcome prediction after surgery. 33,34 These techniques are used to extract features and to perform a decision using electrophysiological signals. To assess seizures with motor phenomena, which is the scope of this paper, motion trajectories of markers and computer vision techniques have been used as feasible methods in recognizing kinematic patterns of seizure.…”
Section: Traditional Approaches To Automatic Epilepsy Evaluationmentioning
confidence: 99%